A bound test approach to cointegration of tourism demand - Habibi, Fateh; Abdul Rahim, Khalid (Science Publications, 2009)
Problem statement: Given the high contribution of tourism industry in the Malaysian economy, Malaysia has a vast view to increase its market share of the international tourist arrivals in the Asia Pacific region. Therefore, this study attempts to investigate the long run and short run demand for tourism from top ten markets (country). Approach: To accomplish this objective the ARDL bound test approach to cointegration was carried out for quarterly time series data from 1998:Q1 to 2007: Q3. A three-stage procedure followed to test the direction of causality. In the first stage the order of integration was tested using the Augmented Dickey-Fuller (ADF) and Phillips Perron (PP) unit root tests. The second stage involved testing for the existence of a long-run equilibrium relationship between arrivals, income, tourism price, tourism substitute price and travel cost. The third stage involved constructing standard Granger-type causality tests augmented with a lagged error-correction term where the series were cointegrated. Results: The result of ADF and PP unit root tests confirmed that all variables were stationary at first difference. In addition the results indicated that a long run relationship and between variables. Conclusion: The results indicated that tourists from these ten countries seem to be highly sensitive to the price and the alternative destinations are complementary to Malaysia. In addition the results showed that the outbreak of Severe Acute Respiratory Syndrome (SARS, 2003) had a negative affects significantly affected Malaysia.